Accuracy of dynamic navigation in implant surgery: A systematic review and meta‐analysis - Wei, Shi‐Min; Zhu, Yu; Wei, Jian‐Xu; Zhang, Chu‐Nan; Shi, Jun‐Yu; Lai, Hong‐Chang (Clinical oral implants research, 2021)
Objective To assess the accuracy of dynamic computer‐assisted implant surgery. Materials and methods An electronic search up to March 2020 was conducted using PubMed, Embase, and the Cochrane Central Register of Controlled Trial to identify studies using dynamic navigation in implant surgery, and additional manual search was performed as well. Clinical trials and model studies were selected. The primary outcome was accuracy. A single‐arm meta‐analysis of continuous data was conducted. Meta‐regression was utilized for comparison on study design, guidance method, jaw, and systems. Results Ten studies, four randomized controlled trials (RCT) and six prospective studies, met the inclusion criteria. A total of 1,298 drillings and implants were evaluated. The meta‐analysis of the accuracy (five clinical trials and five model studies) revealed average global platform deviation, global apex deviation, and angular deviation were 1.02 mm, 95% CI (0.83, 1.21), 1.33 mm, 95% CI (0.98, 1.67), and 3.59°, 95% CI (2.09, 5.09). Meta‐regression shown no difference between model studies and clinical trials (p = .295, 0.336, 0.185), drilling holes and implant (p = .36, 0.279, 0.695), maxilla and mandible (p = .875, 0.632, 0.281), and five different systems (p = .762, 0.342, 0.336). Conclusion Accuracy of dynamic computer‐aided implant surgery reaches a clinically acceptable range and has potential in clinical usage, but more patient‐centered outcomes and socio‐economic benefits should be reported.